Analytical investigation of the behavior of compact and non compact circular tubular composite columns under axial compression - Martarello, Yule Anni Dourado [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Structural elements ensure the stability of buildings by supporting various loads while preserving functionality and aesthetics. Concrete-filled steel tubular (CFST) columns combine the advantages of both materials, offering high load-bearing capacity, excellent seismic performance, and reduced self-weight compared to reinforced concrete columns. The circular section provides effective concrete confinement, delays local buckling, and enhances structural ductility. However, due to the higher slenderness of non-compact sections, their design requires more complex analytical evaluation. In this context, the present study investigates the behavior of compact and non-compact circular CFST columns subjected to axial compression through analytical approaches and comparison with experimental results, using design models from eight international standards. The literature review enabled the compilation of a comprehensive database and the implementation of a calculation tool based on these standards. The database included 1,580 experimental CFST columns covering a wide range of geometric and material parameters. The results demonstrate that the accuracy of normative models is strongly influenced by section slenderness limits, where the discrepancy between experimental and analytical results highlights the need for more refined formulations. The mean ratios between calculated and experimental axial resistances (Ncalc / Nexp) indicated distinct levels of conservatism among the standards. About de compact columns, the Canadian and Australian/New Zealand standards were the most conservative, with mean values of 0.697 and 0.772, respectively. The first presented relatively low coefficients of variation (16%), but for the second standard, the coefficient of variation showed high dispersion (30%). Conversely, the Eurocode 4 and Chinese standards tended to overestimate the load-carrying capacity, especially for non-compact sections, with mean values of 1.176 and 0.959, and higher variability (CV = 41% and 26%, respectively). The updated Brazilian and American standards presented intermediate performance, with mean ratios of 0.808 and 0.806 and CVs of 17%, demonstrating satisfactory agreement with experimental results and balanced conservatism. For non-compact columns, the average ratios were generally higher, confirming that most standards underestimate experimental strengths to a greater extent in slender geometries. Among them, the Australian/New Zealand standard exhibited the lowest coefficient of variation (CV = 13%), indicating high consistency in its predictions. The American and the updated Brazilian standard followed, with slightly higher but still acceptable variability (CV = 17% and 18%, respectively). However, the coefficients of variation remained relatively similar between compact and non-compact groups, indicating that cross-section slenderness primarily affects the accuracy of predictions rather than their dispersion. Overall, the analytical evaluation highlights the sensitivity of CFST column predictions to section slenderness, the definition of local buckling limits, and the consideration of confinement effects, emphasizing the need for refined design provisions for non-compact CFST columns and the development of more accurate and efficient international standards.

Os elementos estruturais garantem a estabilidade das edificações ao suportarem diversas cargas, preservando a funcionalidade e a estética. Os pilares mistos tubulares de aço preenchidos com concreto (CFST) combinam as vantagens de ambos os materiais, oferecendo elevada capacidade resistente, excelente desempenho sísmico e menor peso próprio em comparação aos pilares de concreto armado. A seção circular proporciona confinamento efetivo do concreto, atrasa a flambagem local e aumenta a ductilidade estrutural. No entanto, devido à maior esbeltez das seções não-compactas, o dimensionamento dessas peças requer avaliações analíticas mais complexas. Nesse contexto, o presente estudo investiga o comportamento de pilares mistos tubulares circulares compactos e não-compactos submetidos à compressão axial, por meio de abordagens analíticas e da comparação com resultados experimentais, utilizando modelos de cálculo de oito normas internacionais. A revisão bibliográfica possibilitou a compilação de um banco de dados abrangente e o desenvolvimento de uma ferramenta de cálculo baseada nessas normas. O banco de dados incluiu 1580 pilares mistos CFST experimentais, abrangendo uma ampla faixa de parâmetros geométricos e de materiais. Os resultados demonstram que a precisão dos modelos normativos é fortemente influenciada pelos limites de esbeltez das seções, onde a discrepância obtida entre os resultados experimentais e analíticos evidenciam a necessidade de formulações mais refinadas. Os valores médios entre as resistências axiais calculadas e experimentais (Ncalc / Nexp) indicaram diferentes níveis de conservadorismo entre as normas analisadas. Para pilares mistos compactos, as normas canadense e australiana/neozelandesa foram as mais conservadoras, com valores médios de 0,697 e 0,772, respectivamente. A primeira, apresentou coeficiente de variação relativamente baixos (16%), porém para a segunda norma, o coeficiente de variação apresentou alta dispersão (30%). Por outro lado, as normas europeia e chinesa tenderam a superestimar a capacidade resistente, especialmente para seções não-compactas, com valores médios de 1,176 e 0,959 e maior variabilidade (CV = 41% e 26%, respectivamente). A norma brasileira recente e americana apresentaram desempenho intermediário, com razões médias de 0,808 e 0,806 e CVs de 17%, demonstrando boa concordância com os resultados experimentais e um conservadorismo equilibrado. Para pilares mistos não-compactas, os valores médios foram mais elevadas, confirmando que a maioria das normas tende a subestimar as resistências experimentais em maior grau em geometrias esbeltas. Entre elas, a norma australiana/neozelandesa apresentou o menor coeficiente de variação (CV = 13%), indicando alta consistência em suas previsões. As normas americana e brasileira atualizada apresentaram valores ligeiramente superiores, mas ainda dentro de uma variabilidade aceitável (CV = 17% e 18%, respectivamente). No entanto, os coeficientes de variação permaneceram relativamente próximos entre os grupos de seções compactas e não-compactas, indicando que a esbeltez da seção transversal afeta principalmente a precisão das previsões, e não sua dispersão. De modo geral, a avaliação analítica evidencia a sensibilidade das previsões de pilares mistos CFST à esbeltez da seção, à definição dos limites de flambagem local e à consideração dos efeitos de confinamento, ressaltando a necessidade de aprimoramento das prescrições normativas para pilares mistos CFST não-compactas e do desenvolvimento de normas internacionais mais precisas e eficientes.
Investigação analítica do comportamento de pilares tubulares mistos de aço preenchidos com concreto, compactos e não-compactos, submetidos a força axial de compressão
Keywords: Circular tubular composite columns; Non-compact sections; Axial compression; Analytical model; Pilares mistos tubulares circulares; Seções não-compactas; Compressão centrada; Modelo analítico